PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJARIPS SISWA KELAS IV SDN 18SUNGAI PAKNING KECAMATAN BUKIT BATUKABUPATEN BENGKALIS - Nurul Azmi; Zariul Antosa; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research is motivated still low learning outcomes IPS fourth grade students of SDN 18 Sungai Pakning Kecamatan Bukit Batu Kabupaten Bengkalis, where an average of 60.91 students' learning outcomes which have been established under the KKM is 65. Of the 24 students who completed only 9 people, while 15 the uncompleted. This research is a classroom action research (PTK) conducted aims to improve learning outcomes IPS fourth grade students of SDN 18 Sungai Pakning Kecamatan Bukit Batu Kabupaten Bengkalis to implement cooperative learning model. Instrument of data collection in this thesis is the teacher and student activity sheets and learning outcomes. This paper presents the study results of the data obtained from the average of the results of study before action increased to 12.18% 60.91 to 68.33 in the I. cycle on the second cycle increased to 21,43% with an average of 73.96. The activities of teachers in the first cycle the first meeting to obtain a percentage of 70.83% with the good category. At the second meeting mengaami 75% increase in the percentage of both categories. The next cycle II to the first meeting of teachers activity increased with the percentage of 87.5% is very good category, and the second meeting of the second cycle to increase again with the percentage of 95.83% with a very good category. Activity of students in the first cycle the first meeting of the percentage gain of 37.5% less category.At the second meeting have increased the percentage of 54.16% category enough. At this cycle the students begin to understand the learning activities by implementing cooperative learning model, characterized by the activity of students in the second cycle to the first meeting with a percentage of 75% increases both categories. At the second meeting of the second cycle to increase the percentage of 87.5% is very good category. Results of the study in class IV SDN 18 Sungai Pakning Kecamatan Bukit Batu Kabupaten Bengkalis prove that the implementation of cooperative learning model can improve learning outcomes IPS fourth grade students of SDN 18 Sungai Pakning Kecamatan Bukit Batu Kabupaten Bengkalis.Keywords: Cooperative Learning , IPS Learning Outcomes